Two approaches—one phenomenon—thrombocytopenia after surgical and transcatheter aortic valve replacement. Issue 6 (29th April 2020) - Vogt, Ferdinand; Moscarelli, Marco; Pollari, Francesco; Kalisnik, Jurij M.; Pfeiffer, Steffen; Fittkau, Matthias; Sirch, Joachim; Pförringer, Dominik; Jessl, Jürgen; Eckner, Dennis; Ademaj, Fadil; Bertsch, Thomas; et al.
Abstract: Backgropund and Aim: Postoperative thrombocytopenia after surgical aortic valve replacement (SAVR) or transcatheter aortic valve replacement (TAVR) and aggravating causes were the aim of this retrospective study. Methods: Data of all patients treated with SAVR (n = 1068) and TAVR (n = 816) due to severe aortic valve stenosis was collected at our center from 2010 to 2017. Preprocedural and postprocedural values were collected from electronic patient records. Results: There was a significant drop in platelets in both groups, the TAVR group showed overall superior platelet preservation compared to the AVR group ( P  < .001). In the SAVR subgroup analysis, a significant difference in platelet preservation was observed between the valve types ( P  < .001), particularly with the Freedom SOLO valve. In the TAVR subgroup analysis, the valve type did not influence platelet count (PLT) reduction ( P  = .13). In the SAVR subgroup analyses, PLT was found to be worsened with cardiopulmonary bypass (CPB) duration. Conclusion: Thrombocytopenia frequently occurs after implantation of a biological heart valve prosthesis, with a higher frequency observed in patients after cardiac surgery rather than TAVR. Although some surgical bioprosthetic models are more susceptible to this phenomenon, CPB duration seems to be a major determinant for the development of postoperative thrombocytopenia.